2010
DOI: 10.1182/blood.v116.21.2933.2933
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine In Compassionate Use: Response to Therapy, Survival, and Prognostic Factors In 200 Patients Diagnosed with MDS or AML

Abstract: 2933 Introduction: Survival analysis need of large period of time for getting results. Survival subrogates variables provide with earlier data for clinical decisions. The current treatment paradigm is nowadays how the quality of the different treatment responses impact in patient's survival with the new treatment options. Azacitidine (AZA) is a hypomethilating agent which was available for clinical trials or compassionate use in Spain before receiving it mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This was mainly associated with financial problems and the reimbursement policy in our country. In other series, however, the therapy was usually not stopped unless a CR was achieved [6,7,[11][12][13][14]. Gore et al [16], reported of delayed responses that occurred beyond 9 months in patients who continued to use Aza-C.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was mainly associated with financial problems and the reimbursement policy in our country. In other series, however, the therapy was usually not stopped unless a CR was achieved [6,7,[11][12][13][14]. Gore et al [16], reported of delayed responses that occurred beyond 9 months in patients who continued to use Aza-C.…”
Section: Discussionmentioning
confidence: 99%
“…12, 13, published the Spanish Aza‐C registry results with three different treatment schedules of azacitidine [ group A : Aza‐C 75 mg/m 2 on days 1–5 (every 28 days); group B : Aza‐C 75 mg/m 2 on days 1–5, 8–9 (every 28 days) and group C : Aza‐C 75 mg/m 2 on days 1–7 (every 28 days)]. In their retrospective analysis of 200 patients with MDS and AML the overall response rates ranged between 42.5% and 63.2%, without any statistically significant difference between the three schedules 12. When they analysed the 181 MDS only patients, however, they found overall response rates of 37.7%, 70.6% and 52.2% for groups A, B and C, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In their retrospective analysis, the ORR was 42.5% for 5 days, 63.2% for 5/2/2, and 56.4% for 7 consecutive days without any significant difference between the three schedules. 16 However, when the analysis was restricted only to 181 patients with MDS they reported ORR of 37.7% for 5 days, 70.6% for 5/2/2, and 52% for 7 consecutive days, respectively. 17 The higher ORR that have been reported in the previous two studies using the 5/2/2 schedule could be due to the inclusion of lower-risk patients compared to our study group: 59 and 70% were L-R and INT-1 by IPSS in these studies, respectively, while in our study only INT-2 and H-R patients were included.…”
Section: Discussionmentioning
confidence: 97%